Between Past and Future - Sorin Antohi (Central European University Press, 2000)
""The list of contributors is impressive withnot a single dull chapter...; the editors are to be congratulated for making available such a stimulating and timely, if not timeless, collection"" - Slavic Review ""[T]his is a book that will serve many intellectual tastes and interests, and that will certainly prove thought provoking for anyone who reads it... I recommend it to anybody who wants to witness the analythical depth and span with which the meaning of 1989 can be approached."" - Extremism ...